2000
DOI: 10.1002/(sici)1097-0223(200005)20:5<378::aid-pd815>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of beta-thalassaemia in Pakistan: experience in a Muslim country

Abstract: A service for prenatal diagnosis of beta-thalassaemia was introduced in Pakistan in May 1994. Two renowned Islamic scholars, consulted before the service was introduced, ruled that a pregnancy can be terminated if the fetus is affected by a serious genetic disorder, and if termination is before 120 days (17 weeks) of gestation. During the first 3(1/2) years of the service 300 couples requested the test. Almost all the couples had been informed by their treating doctors. Most diagnoses were made between 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 12 publications
1
60
0
Order By: Relevance
“…As the cost of medical expenses of these patients is provided by the Ministry of Health and Medicine, the government itself is monitoring the prevention programme. Due to cultural and religious restrictions on abortion in Islamic countries, 19,20 the routine prevention of the birth of thalassaemic children by this means was not possible. The religious authorities in Iran have allowed abortion at 16 weeks of gestation for the last three years; however, there are still many limitations for abortion, such as high expenses and inadequate facilities.…”
Section: Discussionmentioning
confidence: 99%
“…As the cost of medical expenses of these patients is provided by the Ministry of Health and Medicine, the government itself is monitoring the prevention programme. Due to cultural and religious restrictions on abortion in Islamic countries, 19,20 the routine prevention of the birth of thalassaemic children by this means was not possible. The religious authorities in Iran have allowed abortion at 16 weeks of gestation for the last three years; however, there are still many limitations for abortion, such as high expenses and inadequate facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Decision making about prenatal diagnosis, however, is multifaceted and it is impossible to generalize (de Montalembert et al, 1996;Modell et al, 1997;Atkin et al, 1998;Ahmed, et al, 2000;Parker et al, 2002;Tsianakas and Liamputtong, 2002). Even among Muslim populations, who demonstrate even greater reluctance to terminate pregnancies than other religious groups, one study has shown that 67 per cent say that they would consider termination following a prenatal diagnosis of thalassaemia (Hewison et al, 2004).…”
Section: Religious Identity and Decision Makingmentioning
confidence: 99%
“…Under Pakistani law, it is illegal to carry out an abortion except if the mother"s life is in danger. However, service providers can seek Fatwas (religious decrees) from religious scholars that give permission for abortion before 120 days gestation in cases where a fetus is affected by a disorder of a "severe nature" (Ahmed, Saleem, Sultana, Raashid, Waqar, & Anwar, 2000). Q-Methodology combines quantitative techniques and analyses with broadly qualitative approaches to sampling and pattern interpretation (Stenner, Watts, & Worrell, 2008;Watts & Stenner, 2005).…”
Section: Introductionmentioning
confidence: 99%